2014
DOI: 10.1063/1.4898057
|View full text |Cite
|
Sign up to set email alerts
|

Weakly relativistic and ponderomotive effects on self-focusing and self-compression of laser pulses in near critical plasmas

Abstract: The spatiotemporal dynamics of high power laser pulses in near critical plasmas are studied taking in to account the effects of relativistic and ponderomotive nonlinearities. First, within one-dimensional analysis, the effects of initial parameters such as laser intensity, plasma density, and plasma electron temperature on the self-compression mechanism are discussed. The results illustrate that the ponderomotive nonlinearity obstructs the relativistic self-compression above a certain intensity value. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Hence, after a certain laser intensity threshold (upper-limit), the beam starts to defocus. [37] By compressing the laser pulse, the laser intensity goes up and reaches the upper-limit, as a result the beam diverges. This is due to the fact that the magnetic field modifies the refractive index of plasma to intensify the nonlinear effects.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, after a certain laser intensity threshold (upper-limit), the beam starts to defocus. [37] By compressing the laser pulse, the laser intensity goes up and reaches the upper-limit, as a result the beam diverges. This is due to the fact that the magnetic field modifies the refractive index of plasma to intensify the nonlinear effects.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…[11−16] The effect of selfcompression mechanism on the self-focusing of a Gaussian laser beam in an unmagnetized plasma has already been investigated by Bokaei and Niknam. [17] They have shown in their work that in the presence of ponderomotive nonlinearity the self-focusing mechanism is obstructed by the self-compression one. Shibu et al [14] have investigated the self-compression of Gaussian laser beam due to the relativistic mass nonlinearity and have observed that the self-focusing mechanism interferes strongly with the non-linear self-compression process.…”
Section: Introductionmentioning
confidence: 99%
“…(22)- (24). The parameters of the laser pulse and plasma are chosen as below, a 0 ¼ 0.1, s 0 ¼ 100 fs, n 0 ¼ 3 Â 10 21 cm À3 , and x ¼ 5 Â 10 15 rad s À1 .…”
Section: Numerical Investigationmentioning
confidence: 99%
“…[18,19] Numerous efforts have been done on the high-intensity laser beam evolution in the plasma. [20][21][22][23][24][25][26][27][28][29] The electromagnetic filamentation instability in the magnetized plasmas taking into account the relativistic electron mass variation and magnetic field perturbations has been studied by Shukla et al [20] Shibu et al have investigated the compression possibility of the laser pulse in a relativistic plasma and observed that the nonlinear self-focusing interferes with the self-compression mechanism. [15] Brandi et al [21] studied the propagation of high-intensity short laser beams in an inhomogeneous plasma.…”
Section: Introductionmentioning
confidence: 99%